From Clicks to Conversions: Optimizing Brand Awareness through Social Media Benchmarking - Yahya, Andi Fauziah; Riana, Mirandha Ariesca; Jannah, Mardiatul; Gunawan, Muhammad Taufan; Syafruddin, Jasmin Anisah; Armayani, Andi (Universitas Pahlawan Tuanku Tambusai, 2024)
The advancement of information technology in Indonesia compels MSMEs to innovate in their online marketing strategies. This study aims to understand the application of benchmarking in social media marketing for brand awareness in MSMEs, focusing on the case study of Pisana Berkah Abadi. Using a descriptive qualitative approach, this research explores the best practices of Buynana Chips and adapts them at Pisana. The results show a significant increase in reach, impressions, and followers after implementing storytelling and interaction content. Benchmarking is proven effective for MSMEs to enhance their marketing strategies and build stronger brand awareness.